A comparison of the orthotic effect of the Odstock Dropped Foot Stimulator and the Walkaide functional electrical stimulation systems on energy cost and speed of walking in Multiple Sclerosis. (November 2015) - Miller, Linda; Rafferty, Danny; Paul, Lorna; Mattison, Paul
Abstract Purpose: Functional electrical stimulation (FES), an assistive device used for foot drop, has been found to improve the speed and energy cost of walking in people with multiple sclerosis (pwMS). This study aims to compare the immediate orthotic effect on walking of two different devices; the Odstock Dropped Foot Stimulator (ODFS) and Walkaide (WA). Method: Twenty pwMS (10 female, 10 male, mean age 50.4 ± 7.3 years) currently using ODFS were recruited. Participants walked for 5 min around an elliptical 9.5 m course at their preferred walking speed; once with ODFS, once with WA and once without FES on the same day of testing. Gait speed, distance and energy cost were measured. Results: There was a statistically significant increase in walking speed for the ODFS (p = 0.043) and a near to significant increase for the WA (p = 0.06) in comparison to without FES. There were no differences between the ODFS and WA in terms of either walking speed (p = 0.596) or energy cost (p = 0.205). Conclusions: This is the first pilot study to compare the effects of two different FES devices on walking. Further research recruiting a larger cohort of FES naive participants is needed. Implications for Rehabilitation Functional electrical stimulation (FES) used for foot drop in multiple sclerosis (MS) is effective in improving the speed of walking. The Odstock Dropped Foot Stimulator and the Walkaide have similar orthotic effects on the speed and energy cost of walking in people with MS. Further research is urgently needed to compare FES devices, recruiting treatment of naive participants for a fully powered RCT.